A dynamic explanation model for human-computer interface - Chalyi, Serhii; Leshchynskyi, Volodymyr; Leshchynska, Iryna (Національний технічний університет "Харківський політехнічний інститут", 2020)
The scientific novelty of the results is as follows. A temporal approach to constructing explanations for the operation of an intelligent system is proposed. The approach describes explanation as a process consisting of a temporally ordered sequence of facts. The order of time for pairs of facts is determined by temporal rules. Such rules may define the explanation process with varying degrees of detail over time, depending on the request for clarification. Detailed explanations reflect the subject area model and include the basic and alternative sequences of actions performed by the intelligent system. The explanation of the basic patterns of the intelligent system makes it possible to interpret the limitations that affect the obt ained solution. The explanation of the system as a whole provides an implicit reflection of the key causal relationships, which allows you to get a simplified interpretation of the results of the intelligent system. A dynamic model of describing explanations based on temporal knowledge for use in the human-computer interface is proposed. The model takes into account the description of actions in the subject area, the patterns of these actions, as well as generalized causal relationships between such patterns. The model provides an opportunity to present the dynamics of the process of functioning of the intelligent system with the required level of detail, as well as change the level of detail to clarify the explanation at the request of the user.

Наукова новизна отриманих результатів полягає в наступному. Запропоновано темпоральний підхід до побудови пояснень щодо роботи інтелектуальної системи. Підхід описує пояснення як процес, що складається із темпорально упорядкованої послідовності фактів. Порядок у часі для пар фактів задається темпоральнимиправилами. Такі правила можуть визначати процес пояснення із різним ступенем деталізації у часі, в залежності від запиту на пояснення. Детальні пояснення відображають модель предметної області і містять у собі базові та альтернативні послідовності дій, що виконує інтелектуальна система. Пояснення базових патернів роботи інтелектуальної системи дає можливість інтерпретувати обмеження, які впливають на отримане рішення. Пояснення роботи системи в цілому забезпечує неявне відображення ключових причинно-наслідкових залежностей, що дозволяє отримати спрощену інтерпретацію результатів роботи інтелектуальної системи. Запропоновано динамічну модель опису пояснень на основі темпоральних знань для використання у людино-машинному інтерфейсі. Модель враховує опис дій у предметної області, патерни цих дій, а також узагальнені причинно-наслідкових зв'язки між такими патернами. Модель забезпечує можливість представлення динаміки процесу функціонування інтелектуальної системи із необхідним ступенем деталізації, а також зміну рівня деталізації для уточнення пояснення за запитом користувача.
Динамічна модель представлення пояснень для людино-машинного інтерфейсу
Keywords: knowledge; knowledge representation; temporal rules; знання; представлення знань; темпоральні правила